2013
DOI: 10.1002/stem.1450
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin neutralization blocks hematopoietic stem cell osteoclastogenesis

Abstract: Bone is a dynamic tissue that is continuously remodeled through the action of formative osteoblasts and resorptive osteoclasts. Chemerin is a secreted protein that activates chemokine-like receptor 1 (CMKLR1), a G proteincoupled receptor expressed by various cell types including adipocytes, osteoblasts, mesenchymal stem cells (MSCs), and macrophages. Previously, we identified chemerin as a regulator of adipocyte and osteoblast differentiation of MSCs. Herein we examined the role of chemerin in Lin 2 Sca11 c-ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 65 publications
4
63
0
5
Order By: Relevance
“…As expected, RANKL induced marked osteoclastic differentiation in the RAW 264.7 cells, as evidenced by enhanced TRAP staining [18] (Fig. 1A), and increased mRNA and protein expression of NFATC1 and TRAF6, which are markers of mature osteoclasts [19,20] (Fig. 1B, C).…”
Section: Mir-218 Was Downregulated In Osteoclastogenesissupporting
confidence: 79%
“…As expected, RANKL induced marked osteoclastic differentiation in the RAW 264.7 cells, as evidenced by enhanced TRAP staining [18] (Fig. 1A), and increased mRNA and protein expression of NFATC1 and TRAF6, which are markers of mature osteoclasts [19,20] (Fig. 1B, C).…”
Section: Mir-218 Was Downregulated In Osteoclastogenesissupporting
confidence: 79%
“…Aside from intrinsic effects on MSC differentiation, adipocytes have the potential to impact the development and function of other cell types in bone through the paracrine actions of secreted biologically active signaling molecules (adipokines). Several studies have reported that adipocyte-conditioned media samples suppress the formation of osteogenic lineages from MSCs [2628] and promote osteoclast formation from HSCs [5, 29]. This indicates that adipocyte-derived factors can influence the development of key effectors of bone remodeling and thereby bone mass and skeletal integrity.…”
Section: Influence Of Adipocyte-secreted Signaling Molecules On Bone mentioning
confidence: 99%
“…Chemerin activation of its cognate receptor chemokine-like receptor 1 (CMKLR1) in bone marrow MSCs resulted in PPARγ-mediated β-catenin ubiquitination that abrogated basal osteogenic Wnt signaling and promoted the adipogenic PPARγ signaling in MSCs [32, 33•]. In addition, the paracrine actions of chemerin through activation of CMKLR1 expressed by HSCs promoted osteoclastogenic differentiation and matrix resorption [29]. Conversely, other adipokines such as C1q/tumor necrosis factor (TNF)-related protein-3 (CTRP3) inhibit osteoblast-mediated osteoclastogenic differentiation thereby disrupting the coordination between bone formation and resorption [34].…”
Section: Influence Of Adipocyte-secreted Signaling Molecules On Bone mentioning
confidence: 99%
“…Osteoporosis is carried out by excessive bone destruction by osteoclasts coupled with insufficient bone formation by osteoblasts, resulting in reduction of bone mass and low trauma fractures [1,2]. MicroRNAs (miRNAs) are evolutionarily conserved, small (~22 nucleotides), singlestranded non-coding RNAs that silence the expression of specific gene by base-pairing to the 3'-untranslated regions of target mRNAs on post-transcriptional level [3][4][5].…”
Section: Introductionmentioning
confidence: 99%